PERBANDINGAN PARTIKEL DE çš„ BAHASA MANDARIN DENGAN KATA BERFUNGSI SAMA DALAM BAHASA INDONESIA - Junaeny, Arini (Interference: Journal of Language, Literature, and Linguistics, 2020)
Abstract. Mandarin is one of the most widely used languages in the world. During the learning process, mother language sometimes influences second language learning. Therefore it is necessary to compare the rules of linguistic or comparative linguistics. This study uses a qualitative description method. The word "yang" in Indonesian has a function similar to the de çš„ particle in Mandarin. The similarities, that is, has a function as a link between the core word and the attributive word which also describes the characteristics, nature, emphasis. In Mandarin the de-particle is behind the attributive word, while the Indonesian word "yang" is in front of the attributive word. Not all the words de çš„ can be commensurate with the word "yang", the word de çš„ can be translated or matched with several words in Indonesian depending on the meaning and function, such as "buatan", "ciptaan", "milik".